If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -3 = -0.5x + 3 Reorder the terms: -3 + x = -0.5x + 3 Reorder the terms: -3 + x = 3 + -0.5x Solving -3 + x = 3 + -0.5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.5x' to each side of the equation. -3 + x + 0.5x = 3 + -0.5x + 0.5x Combine like terms: x + 0.5x = 1.5x -3 + 1.5x = 3 + -0.5x + 0.5x Combine like terms: -0.5x + 0.5x = 0.0 -3 + 1.5x = 3 + 0.0 -3 + 1.5x = 3 Add '3' to each side of the equation. -3 + 3 + 1.5x = 3 + 3 Combine like terms: -3 + 3 = 0 0 + 1.5x = 3 + 3 1.5x = 3 + 3 Combine like terms: 3 + 3 = 6 1.5x = 6 Divide each side by '1.5'. x = 4 Simplifying x = 4
| 5-9x=-4x | | 3z-2z+8= | | 3x+9=-1Y+29 | | 2x^3-5x-9=0 | | 12-42=3(x-2)-9 | | 100=33+x | | 15=(5k-13) | | 2x^2=1080 | | 32y^2+5y+6y= | | 40=-8(x+7) | | 700=84+28d | | -3(r+8)=48 | | 2x=250+x | | -15x+32=x | | 15w-19w=24 | | .5y-1=.33 | | -(3x+4)+15=6-4x | | (6-4)(6+3)=18 | | 37-13=4(x-6) | | 38=-1X | | y=3x+(2x-1) | | 40x+x^2=624 | | 7(2*-3)+3=24 | | 90+51=2x+1 | | 5/6h-7/13=-3/4h-13/6 | | 2x+6=-6x+54 | | 2y+3(x+2)=-5 | | x/2(28-x)=96 | | -38-(-49)=x/12 | | 6x+2+107=163 | | 2y=y+2 | | -3x-2=30 |